The Effect of Cash Conversion Cycle on Company Profitability: A Study on Indonesian Food and Beverage Listed Companies - Budi Oktavianus Yusan; Sarwo Edy Handoyo (Sultan Publisher, 2024)
The Indonesian Food and Beverage industry is a dynamic and pivotal sector in the Indonesian business ecosystem, contributing significantly to the nation's economic growth and reflecting its cultural diversity. This paper delves into the relationship between the Cash Conversion Cycle and the profitability of Indonesian Food and Beverage listed companies. By examining this intricate connection, the study aims to provide valuable insights for financial managers, policymakers, investors, and researchers within this sector. This study used panel data regression with a purposive sampling method with a total of 687 samples that spans from 2007 until 2022. Data processing in this study uses Eviews 9. The research adopts Gross Profitability as a precise measure closely linked to working capital management and tests hypotheses related to the Cash Conversion Cycle components, including Days of Inventory Outstanding, Days of Sales Outstanding, and Days of Payable Outstanding. The findings reveal that Days of Sales Outstanding significantly and negatively impacts Gross Profitability, emphasizing the importance of efficient accounts receivable collection for profitability. Days of Inventory Outstanding, while marginally significant, also shows a negative association with Gross Profitability. In contrast, Days of Payable Outstanding does not exhibit statistical significance in explaining variations in Gross Profitability. These insights provide valuable guidance for managers in optimizing working capital management. Moreover, the paper recommends future research directions, including long-term analysis, industry-specific exploration, the influence of macroeconomic factors, comparative studies, and qualitative research to deepen our understanding of the Cash Conversion Cycle 's role in the Indonesian Food and Beverage industry and enhance financial management practices.